2020
DOI: 10.3389/fpsyg.2020.00377
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Calm and Carrying On: Relating Affect Spin and Pulse to Complex Skill Acquisition and Adaptive Performance

Abstract: The purpose of this laboratory study involving repeated measures of emotion as 214 undergraduates (58.4% male) learned a complex video game was to address the need for empirical research on dynamic personality constructs by examining how two aspects of affect variability-spin and pulse-explain variance in skill acquisition and adaptive performance. Spin refers to within-person fluctuations in affect pleasantness and activation potential. Pulse refers to within-person fluctuations in affect intensity. Despite r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
(121 reference statements)
1
10
0
Order By: Relevance
“…Consequently, uncertainty resulting from identifying change and the corresponding stress it engenders may influence the extent to which employees move beyond the initial search process as well as how successful their efforts to adapt may be in the long-term (Shoss et al, 2012). Although research has generally focused on more distal individual differences constructs instead of in-situ emotional or affective experiences, several findings do point to stress, emotions, and emotion regulation as helpful in the adaptation process (e.g., Acikgoz & Latham, 2020; Bande & Fernández-Ferrín, 2015; Richels, Day, Jorgensen, & Huck, 2020).…”
Section: Progression Through the Process Feedback Loops And Dynamic I...mentioning
confidence: 99%
“…Consequently, uncertainty resulting from identifying change and the corresponding stress it engenders may influence the extent to which employees move beyond the initial search process as well as how successful their efforts to adapt may be in the long-term (Shoss et al, 2012). Although research has generally focused on more distal individual differences constructs instead of in-situ emotional or affective experiences, several findings do point to stress, emotions, and emotion regulation as helpful in the adaptation process (e.g., Acikgoz & Latham, 2020; Bande & Fernández-Ferrín, 2015; Richels, Day, Jorgensen, & Huck, 2020).…”
Section: Progression Through the Process Feedback Loops And Dynamic I...mentioning
confidence: 99%
“…Given the speed with which daily scenarios vary and the number of novel demands which must be coped with in short periods of time, knowing the effects of the capacity of adaptation to change of the population may be beneficial to both immediate and long-term psychological health [ 6 ]. In this respect, models have been proposed to establish the dimensions and factors that intervene in the process of adaptation to change, but linked to transcendental life events (such as the appearance of a disability, birth of a child or death of a spouse) or employment demands [ 46 , 47 ]. This study proposed construction of a model of adaptation to change in everyday events and circumstances, which would enable a scale to be designed for evaluating the response to challenges and changing circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in knowing the capacity of individuals to adapt to change has led to studies seeking to establish the cognitive and emotional dimensions giving rise to this variable. However, analysis of the factors that enable success in new situations and unexpected changes in one’s environment have focused mainly on the job context [ 46 , 47 ]. Hedonic adaptation to important life events has also been analyzed [ 48 ], but not to changes in environmental demands with less transcendence in life than the birth of a child or the death of a family member.…”
Section: Introductionmentioning
confidence: 99%
“…Employee's adaptivity helps companies to build a sustained performance and seize new opportunities in the market (Babel'ová et al 2015;Babel'ová and Stareček 2021). Moreover, there is an increasing body of research on the determinants of individual adaptive performance (Richels et al 2020). In detail, Baard et al (2014) reported a growth of current research interest in individual characteristics and learning processes that boost individual adaptive performance.…”
Section: Active Learning and Individual Adaptive Performancementioning
confidence: 99%
“…Employee capabilities are also cited as a main factor in innovation processes, becoming the source of ideas and creativity underpinning a company's competitive advantage through a learning process (De Spiegelaere et al 2015). Meanwhile, employee learning is also beneficial in supporting the skill acquisition process necessary to meeting organizational needs in adopting digital technological advancements (Richels et al 2020). These authors also stated that the learning process constitutes a switching-driven behavior within an individual adaptive mechanism.…”
Section: Introductionmentioning
confidence: 99%